Characterization of Silver Nanoparticle In Situ Synthesis on Porous Sericin Gel for Antibacterial Application. (26th April 2016) - Tao, Gang; Liu, Lina; Wang, Yejing; Chang, Huaipu; Zhao, Ping; Zuo, Hua; He, Huawei
Abstract : Sericin from Bombyx mori cocoon has good hydrophilicity, reaction activity, biocompatibility, and biodegradability, which has shown great potentials for biomedical materials. Here, an ultraviolet light-assisted in situ synthesis approach is developed to immobilize silver nanoparticles on the surface of sericin gel. The amount of silver nanoparticles immobilized on the surface of sericin gel could be regulated by the irradiation time. The porous structure and property of sericin gel were not affected by the modification of AgNPs, as evidenced by the observation of scanning electron microscopy, X-ray diffractometry, and Fourier transform infrared spectroscopy. Differential scanning calorimetry analysis showed that the modification of AgNPs increased the thermal stability of sericin gel. The growth curve of bacteria and inhibition zone assays suggested that the sericin gel modified with AgNPs had good antimicrobial activities against both Gram-negative and Gram-positive bacteria. This novel sericin has shown a great potential for biomedical purpose.